Impact Of Preoperative Nutritional Optimization on Postoperative Outcomes - patil, Sanjeev; Allad, Anveerbhadra; Puranik, Vijaykumar; kumar, Nalla Shriram (Journal of Neonatal Surgery, 2025)
Background: Malnutrition and suboptimal nutritional status are recognized as major risk factors for adverse surgical outcomes. Patients undergoing both elective and emergency surgeries often present with varying degrees of nutritional deficiencies that can impact wound healing, immune competence, and overall recovery. There is growing evidence that preoperative nutritional optimization programs may enhance postoperative recovery, reduce complications, and improve hospital resource utilization. Methods: A systematic literature review and retrospective analysis of a single-center cohort were conducted to evaluate the effects of targeted preoperative nutritional interventions on postoperative outcomes. Data on postoperative complications, length of hospital stay, and readmission rates were collected. Additionally, patient compliance with nutritional protocols and changes in measurable nutrition indices, such as albumin and body mass index (BMI), were monitored. Results: In total, 280 surgical patients (185 receiving nutritional optimization vs. 95 controls) were included. Patients who received individualized nutritional counseling and supplementation demonstrated a significant reduction in postoperative complications, including surgical site infections and anastomotic leaks. The intervention group also showed a shorter average hospital length of stay (p < 0.01) and lower readmission rates within 30 days (p < 0.05). There were notable improvements in the levels of serum albumin and prealbumin among the intervention group. Conclusion: The findings support the hypothesis that targeted preoperative nutritional interventions can significantly improve postoperative outcomes. Early identification of nutritional risk and timely optimization strategies are recommended as essential components of the surgical care continuum. These measures may lead to fewer complications, reduced hospital stays, and an overall enhancement in patient recovery and resource management.